Implementation of Fulfilling The Rights of Adopted Children in The Inheritance Law System According to A Compilation of Islamic Law and Civil Law - Muhaimi Muharrar (Civiliza Publishing, 2023)
Adoption of children in Indonesia has been around for a long time; until now, adoption is regulated in the Compilation of Islamic Law and also in Staatsblad 1917 No. 129. In the KHI and the Civil Code, the position of adopted children is differentiated, whereas in the KHI, adopted children cannot be equated with biological children. Whereas in the Civil Code, Adopted children have the same position as biological children. These differences certainly have legal consequences for the inheritance rights of adopted children, where whether or not the adoption of a child is valid according to the KHI and the Civil Code will impact the adopted child's rights to the inheritance of his or her adoptive parents. The aim of writing this thesis is to see the implementation of fulfilling the inheritance rights of adopted children according to the KHI and the Civil Code by looking at what the Law is like in Indonesia. The research method used is normative legal research by reviewing library materials. The results of the research found differences in the definition of child adoption in the KHI and the Civil Code. This is one of the factors in not fulfilling the inheritance rights of adopted children. The importance of harmony between KHI and the Civil Code, as well as other statutory provisions in defining child adoption, is because it will impact the rights of adopted children and adoptive parents if the child's adoption is deemed invalid. Therefore, the definition of child adoption must refocus on the purpose of child adoption itself, namely to improve the welfare of the child and take care of and maintain it so that they can live a good life, which, if this has happened and can be proven then the adoption should be legal as follows: legal consequences.